1993
DOI: 10.1007/bf01977402
|View full text |Cite
|
Sign up to set email alerts
|

Chondrotoxicity of quinolones in vivo and in vitro

Abstract: Chondrotoxicity is a rare toxicological finding which is observed in dogs after administration of quinolone antibacterials. To study this effect chondrocytes from articular cartilage of dogs were isolated, and incubated with quinolone derivatives. The effects on cell viability, mitochondrial dehydrogenase, and proteoglycan synthesis were determined. These results were compared with in vivo findings in dogs treated with these quinolones. It was concluded that inhibition of mitochondrial dehydrogenase activity a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
22
0

Year Published

1994
1994
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 17 publications
1
22
0
Order By: Relevance
“…Together, the results of the present study suggest that fluoroquinolone-induced tendinopathies occur by the same pathophysiological pathways as those described for cartilage (12,24). Previous reports suggested compromised mitochondrial activity, and a precocious stimulation of the oxidative metabolism within immature articular chondrocytes was also described (11,33), with both of these resulting in the generation of reactive oxygen species.…”
Section: Discussionsupporting
confidence: 82%
“…Together, the results of the present study suggest that fluoroquinolone-induced tendinopathies occur by the same pathophysiological pathways as those described for cartilage (12,24). Previous reports suggested compromised mitochondrial activity, and a precocious stimulation of the oxidative metabolism within immature articular chondrocytes was also described (11,33), with both of these resulting in the generation of reactive oxygen species.…”
Section: Discussionsupporting
confidence: 82%
“…LVFX is therefore thought to affect the mitochondrial function of cultured chondrocytes, leading to impaired production of ATP. Concerning the effect of quinolones on mitochondrial functions of chondrocytes, Hildebrand et al (14) used a 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyl-tetrazolium bromide assay to show that quinolones inhibit mitochondrial dehydrogenase activity in cultured chondrocytes of dog articular cartilage. Hayem et al (13) reported that oral administration of OFLX and pefloxacin increased the respiratory burst of chondrocytes in juvenile rabbits, suggesting the generation of reactive oxygen species.…”
Section: Discussionmentioning
confidence: 99%
“…On the basis of their findings, Stahlmann et al suggested that a possible mechanism of this quinolone chondrotoxicity may be impairment of mitochondrial DNA metabolism. Against this, recent in vitro and ex vivo studies have shown that the synthesis of proteoglycans and collagen and the mitochondrial function of chondrocytes are susceptible to inhibition in the presence of quinolones (7,13,14,26). Meanwhile, Stahlmann et al (28) subsequently reported another hypothesis, namely, that by forming stable chelate complexes with magnesium, quinolones may affect the electrolyte balance, impair the function of integrins, and cause degeneration of the matrix, thereby leading to severe damage of articular cartilage.…”
mentioning
confidence: 99%
“…In vitro studies with human lymphocytes exposed to enrofloxacin (ENR) and ciprofloxacin revealed an increase in the chromosomal aberrations, detected as chromatid and chromosome breaks and gaps (Gorla et al, 1999). FQs have been reported to cause neonatal alterations in articulation cartilages, bone growth and tendons, both in humans and animals (Patterson, 1991;Gough et al, 1992;Hildebrand et al, 1993;Forster et al, 1996;Simonin et al, 1999;Stahlmann, 2003;Lemus et al, 2009).…”
Section: Introductionmentioning
confidence: 99%